(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Cemba (Acacia rugata (Lam.) Fawc. Rendle) belongs to the genus acacia. The use of cemba leaves as a spice for traditional dishes in Enrekang Regency has many health benefits. This study aims to dechlorophyllated cemba leaf extract and screen for antioxidant activity testing using several methods. Determination of antioxidant activity using free radical scavenging 1,1-diphenyl picryl hydrazine (DPPH), measurement of phenolic content, and measurement of flavonoid content. The results showed that the free radical scavenger in quercetin was IC50 6.787 µg/mL, a free radical scavenger in dechlorophyllated cemba leaf extract of IC50 349.65. µg/mL total phenolic content of 611.9 mg GAE/g extract and total flavonoid content of 74.8 mgQE/g extract. Based on the IC50 value, the dechlorophyllated Cemba (Acacia rugata (Lam.) Fawc. Rendle) leaf extract has a fragile antioxidant intensity, whereas quercetin as a comparator has a very strong antioxidant intensity. Therefore, dechlorophyllated cemba leaf extract has antioxidant activity.